German lyric diction workbook : a graded method of phonetic transcription that employs frequently occurring words from German art song literature : instructor's manual - Montgomery, Cheri (S.T.M. Publishers, 2013)
This resource allows easy memorization of German Lyric Diction Rules. It is designed for singers, it is excellent for instructors.